Un estudio del impacto de la UNESCO y el Banco interamericano de desarrollo en los procesos de revitalización de los centros históricos latinoamericanos y caribeños: el caso de la zona colonial de Santo Domingo (República dominicana) - Vildan Bahar Tuncay (Études Caribéennes)
There are numerous case studies and collective works that looked for a greater understanding of the revitalization processes of the Latin American historical centers. In this documentation, the Caribbean historical centers are almost nonexistent excluding Havana and Cartagena. Also, the impact of the international organizations such as the United Nations Educational, Scientific and Cultural Organization and the inter-American Development Bank deeply involved in these revitalization processes, has been sub-explored. In this context, according to the hypothesis is that the impact of above mentioned organizations is not only limited to the funding of the revitalization and to the promotion of a type of management focused on efficiency and economic sustainability. It also implies a normative and valorative dimension of urban management promoting and conditioning schemes of normalization, homogenization and professionalization. In order to validate/invalidate the hypothesis, the article has selected the case study of the colonial zone of Santo Domingo, the capital of the Dominican Republic.